A maturity model for measuring digital transformation of archives and libraries - Marquet, Andreas (Qualitative and Quantitative Methods in Libraries, 2021)
The digital transformation is a process that has impact on several fields and thus has technological, economical, and also social dimensions. Even the speed of developments in different areas is varying. For libraries and archives the digital transformation is a major challenge as they are affected by the way they work and interact with their customers as well as digitized and digital born artefacts are relatively new objects for long term preservation. For years the library and the archives of social democracy (AdsD) of the Friedrich-Ebert-Stiftung (FES) have been working in close cooperation but were divided into two separate departments. In 2018, it was decided to reunite the both of them. Against the background of this process, the maturity model of digital transformation was developed for both, libraries and archives as a comprehensive approach. Its dimension locates the digital transformation in the management area where it should be part of a superior strategy. The maturity model for digital transformation is an approach for its contextualization within this strategy and thus should be considered as one method among others. It is a tool in a tool box that gives insight into the libraries and the archives status to consolidate and prioritize next steps. As there are several fields that are affected by the digital transformation, the maturity model covers 4 dimensions: technologies, processes, organization, employees. It is designed as a self assessment questionnaire with a six-step-range ordinal scale that identifies strengths and weaknesses. The result of this self assessment enables to highlight the different levels of progression within and among these dimensions and lays the foundation for further conclusions.